New technologies and the demand for medium qualified labour in Germany - Peter Jacobebbinghaus; Thomas Zwick (Zentrum für Europäische Wirtschaftsforschung (ZEW), 2001)
The literature on skill-biased technological change concentrates on highly skilled and unskilled employees. It is unclear, however, if the employment opportunities of the majority of the labour force in Germany-employees with a degree from the dual apprenticeship system-increase or not. In addition, estimation and data problems are addressed in a topical and rich data set. The paper shows that innovation expenditures and investments in information and communication technologies lead to lower medium skilled employee shares, whereas other investments lead to higher shares.
Keywords: O32; C24; J23; 330; Dual apprenticeship system; qualification demand; innovation; CLAD; SCLS; Facharbeiter; Arbeitsnachfrage; Innovation; Technischer Fortschritt; Schätzung; Deutschland